Hypolipidemic effect of atorvastatin and phytotherapy on rat prostate - A histological study - Erieg A. Mohamed; Eugenia Dumitrescu; Florin Muselin; Alexandru O. Doma; Romeo T. Cristina (Medicamentul Veterinar, 2022)
The prostate is an accessory gland and a component of the male reproductive system. This is found only in some species of mammals and differs morphologically, chemically, and physiologically between species. This paper describes in chapter 1, the basic elements of the prostate (structure, functions, macroscopic and histological characteristics). In chapter 2, the description and activity of atorvastatin are presented, and in chapter 3, two recognized phytotherapeutic remedies are presented: sea buckthorn and grapes (in the form of the compound). In the second part, a study is proposed that investigates the effect of fat consumption on the histological structure of the prostate in a murine model. Through histological investigation of the prostate, this study aimed to comparatively evaluate whether atorvastatin has any healing role on the prostate mirrored in cytoarchitecture and also what is the role of phytotherapy on prostate cytoarchitecture.